2018
DOI: 10.1108/jhti-02-2018-0010
|View full text |Cite
|
Sign up to set email alerts
|

The impact of manager training on employee turnover intentions

Abstract: Purpose There are decades of research analyzing turnover in the hospitality industry and yet it remains nearly double other industries. Whereas previous studies have analyzed training and its impact on turnover, the purpose of this paper is to look at the direct relationship between training at the management level and how this impacts their direct employees’ turnover intentions. Design/methodology/approach This study utilized annual evaluation data from two luxury resorts in the southeast USA. Exploratory f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 64 publications
3
41
1
4
Order By: Relevance
“…The results of this study are consistent with the results of research conducted by Malek, et al (2018), Youngsoo Choi and Duncan R.Dickson (2014), Cheng.et.al. (2013), Mustafa Kesen (2016), Anwar Prabu Mangkunegara and Abdul Waris (2015) and Idrees.et.al (2015) because it is in accordance with the theory put forward by Gomez FC (2010: 42), William H. Mobley (2011: 159) and Mangkunegara (2011: 57).…”
Section: Discussing 1) Compensation Has Positive and Significant Effesupporting
confidence: 92%
See 1 more Smart Citation
“…The results of this study are consistent with the results of research conducted by Malek, et al (2018), Youngsoo Choi and Duncan R.Dickson (2014), Cheng.et.al. (2013), Mustafa Kesen (2016), Anwar Prabu Mangkunegara and Abdul Waris (2015) and Idrees.et.al (2015) because it is in accordance with the theory put forward by Gomez FC (2010: 42), William H. Mobley (2011: 159) and Mangkunegara (2011: 57).…”
Section: Discussing 1) Compensation Has Positive and Significant Effesupporting
confidence: 92%
“…From the results of the analysis conducted by Malek, et al (2018), Youngsoo Choi and Duncan R. Rickson (2014), Cheng.et.al. (2013), although using their respective approaches it can be concluded that there is an influence from the independent variable of training on the dependent variable is job satisfaction.…”
Section: Effect Of Training On Job Satisfactionmentioning
confidence: 99%
“…Dalam rangka upaya mencapai suksesi kepemimpinan yang tepat dan efisien, maka organisasi perlu melakukan pengembangan Sumber Daya Manusia dalam bentuk training and development, baik secara formal ataupun informal, terprogram atau mendesak. Malek, Kline, & DiPietro, (2018) training dan style manajemen memiliki hubungan negatif yang signifikan dengan niat turnover karyawan. Artinya, semakin baik organisasi berinvestasi untuk training karyawan maka akan ada pengurangan niat turnover karyawan di dalamnya.…”
Section: Pendahuluanunclassified
“…Turnover intentions merupakan keinginan atau niat hati yang ingin keluar dari organisasi dengan berbagai alasan, niat untuk mencari alternative pekerjaan yang lebih baik, ataupun niat untuk berhenti atau tinggal di perusahaan saat ini (Huang & Su, 2016;Lu, Lu, Gursoy, & Neale, 2016;Malek et al, 2018). Menurut Mittal, (2016), turnover intentions menjadi suatu tantangan untuk organisasi yang tidak hanya berdampak pada produktifitas tetapi juga pada profit perusahaan.…”
Section: Pendahuluanunclassified
“…The importance of training middle skill managers and supervisors in key areas is critical to the short-term recovery from COVID-19 related challenges. Leaders and managers have direct impact on the overall work environment and have been found to significantly influence employee turnover (Malek et al, 2018). The crucially important middle skill workforce must be retained (National Science Board, 2019).…”
Section: Future Researchmentioning
confidence: 99%